HOW TO COMMUNICATE LIVESTOCK HAZARD? AN APPROACH TO IMPROVE FARMERS’ RISK PREPAREDNESS - Roni Jayawinangun; Dikky Indrawan; Deddy Cahyadi Sutarman (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Poultry industry is faced with a relatively high risk especially for small scale poultry farmers. Therefore, preparedness is needed to deal with risks. Communication in poultry is s essential. Its shown by one of the strategies of national preparedness for facing influenza pandemic, namely communication, information, and education (risk communication). Communication can improve the level of knowledge of farmers. The perceived needs of farmers that emerged include knowledge for a broader implementation of essential biosecurity. This paper aims to find out the standard form of small scale farmers communication with stakeholder and the impact of communication to improve farmers' risk preparedness. The selection of respondents used convineince sampling techniques to 33 farmers. Data analysis used descriptive analysis to found preparedness and communication that is done to reduce hazards. This study found that access communication farmers are Technical Support and Nucleus with two communication approaches, such as technical guidance and personal explanation. The contents of the communication consist of poultry health management, productivity, medicine, biosecurity, cleanliness the cage, and good farming practice. In general, small-scale farmers' preparedness activities in the Bogor district are limited to cleaning the cage regularly and cleaning cage after harvesting. Farmer with more communication activities has a positive impact on preparedness to face risks, especially related to restricting cage access, awareness of cage hygiene, and vaccination. Keywords: preparedness, hazard, livestock, communication